Systematic Literature Review On Social Support System For Labor Market Participation Of Mothers (Architecture Image Studies, 2026)
Motherhood penalty refers to the negative impact of maternity on women’s career, which implicates the inferior status of women in labor market. To improve women’s situation in labor market participation, multiple social support measures should be introduced including sharing childcare responsibility and career sustaining to help mothers achieve a work-family balance. This study aims to systematically review and analyze the social practice applied to support mothers’ labor force participation. By adopting a scoping review method, this study uses Web of Science, Scopus and Google Scholar as the main database in searching for relevant articles. The thematic analysis uncovers the constitution of current social support system for mothers’ labor market participation, which crosses the public and private sphere, as well as its multiple functions, which potentially provide framework for future research in this topic related fields.